The world needs less plastic: the role of psychological distance and self-efficacy in environmental messages - Cooper, Kathryn E.; Brinkerhoff, Laurel; Landreville, Kristen D. (Frontiers in Communication, 2025)
This study examines the role of lowering psychological distance and increasing self-efficacy around plastic pollution through environmental media messages. Participants (N = 215) were randomly assigned to watch a short video (30–60 s) that was either generalized or localized to the state of the participant’s residency and that did or did not include a self-efficacy message in this 2 × 2 between-subjects experiment. Results indicate that message localization lowers psychological distance and including self-efficacy messages increase self-efficacy. Both led to increased message-consistent attitudes and thus increased behavioral intentions to reduce plastic waste and promote the same behaviors in others.